KAJIAN AKADEMIK DARI SUDUT LANDASAN FILOSOFIS, SOSIOLOGIS DAN YURIDIS RANCANGAN PERATURAN DAERAH TENTANG PEMBERIAN INSENTIF DAN KEMUDAHAN INVESTASI DAERAH DI KABUPATEN INDRAGIRI HILIR - wahyuni, Fitri; Wandi, Wandi; Muhsin, Muhsin; Syarifuddin, Syarifuddin (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2024)
One of the Government Affairs which falls under the authority of the Regional Government is to carry out Mandatory Government Affairs which are not related to Basic Services, namely Investment as regulated in Article 12 paragraph (2) point I of Law Number 23 of 2014 concerning Regional Government. To encourage community and private sector participation, Regional Government administrators can provide incentives and/or facilities to the community and/or investors as regulated in Regional Regulations (PERDA). Drafting regional regulations must begin with conducting academic studies from philosophical, sociological, and juridical aspects. This research is normative legal research by collecting secondary data which is analyzed using the concept of deductive logic. Academic studies from the philosophical basis of the formation of this Regional Regulation are in order to create a prosperous society as the state's goal in the Preamble to the 1945 Constitution of the Republic of Indonesia through investment instruments. From a sociological point of view, the formation of this Draft Regional Regulation means that there is a lot of regional potential that can be offered to investors or the public if they want to invest their capital or carry out business activities. However, attracting the interest of investors or the public requires extra efforts, such as through providing incentives or providing various business conveniences. From a juridical point of view, the formation of this Draft Regional Regulation is to carry out the mandate as well as freedom from higher regulations such as Law Number 23 of 2014 concerning Regional Government and its amendments, and Government Regulation Number 24 of 2019 concerning Providing Incentives and Facilitation of Investment in the Regions. which gives authority to regions to be creative and provide solutions in attracting investment to their regions to support development and improve community welfare. Salah satu Urusan Pemerintahan yang menjadi kewenangan Pemerintah Daerah adalah menyelenggarakan Urusan Pemerintahan Wajib yang tidak berkaitan dengan Pelayanan Dasar, yakni Penanaman Modal sebagaimana diatur dalam Pasal 12 ayat (2) butir I UU Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Untuk mendorong peran sertamasyarakat dan sektor swasta tersebut penyelenggara Pemerintahan Daerah dapat memberikan insentif dan/atau kemudahan kepada masyarakat dan/atau investor yang diatur dalam Peraturan Daerah (PERDA). Dalam penyusunan rancangan peraturan daerah haruslah dimulai dengan melakukan kajian akademik dari aspek Filosifis, sosiologis dan yuridis. Penelitian ini merupkan penelitian hukum normatif dengan mengumpulkan data-data secara sekunder yang dianlisis dengan konsep logika deduktif. Kajian akademik dari sudut landasan Filosofis pembentukan Peraturan Daerah ini adalah dalam rangka mewujudkan masyarakat yang sejahtera sebagaimana tujuan negara dalam Pembukaan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 melalui instrumen investasi. Dari sudut sosiologis pembentukan Rancangan Peraturan Daerah ini adalah bahwa banyak potensi daerah yang dapat ditawarkan kepada Investor atau Masyarakat apabila ingin menanamkan modalnya atau melakukan kegiatan usaha. Namun untuk menggiring minat Investor atau Masyarakat memerlukan upaya ekstra seperti melalui pemberian Insentif atau memberikan berbagai kemudahan berusaha. Dari sudut yuridis dalam pembentukan Rancangan Peraturan Daerah ini adalah menjalankan amanat sekaligus keleluasaan dari peraturan-peraturan yang lebih tinggi seperti Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah berikut perubahannya, dan Peraturan Pemerintah Nomor 24 Tahun 2019 tentang Pemberian Insentif dan Kemudahan Investasi Di Daerah yang memberikan kewenangan bagi daerah untuk berkreasi dan solutif dalam menarik investasi ke daerahnya guna mendukung pembangunan dan peningkatan kesejahteraan masyarakat.